Mesenchymal Stem Cells: Signaling Pathways in Transdifferentiation Into Retinal Progenitor Cells - Hamid Aboutaleb Kadkhodaeian (Basic and Clinical Neuroscience, 2021)
Several signaling pathways and transcription factors control the cell fate in its in vitro development and differentiation. The orchestrated use of these factors results in cell specification. In coculture methods, many of these factors secrete from host cells but control the process. Today, transcription factors required for retinal progenitor cells are well known, but the generation of these cells from mesenchymal stem cells is an ideal goal. The purpose of the paper is to review novel methods for retinal progenitor cell production and selecting a set of signaling molecules in the presence of adult retinal pigment epithelium and extraocular mesenchyme acting as inducers of retinal cell differentiation.